The Retromer Complex and Sorting Nexins in Neurodegenerative Diseases - Zhang, Hongfeng; Huang, Timothy; Hong, Yujuan; Yang, Weijie; Zhang, Xian; Luo, Hong; Xu, Huaxi; Wang, Xin (Frontiers in Aging Neuroscience, 2018)
The retromer complex and associated sorting nexins (SNXs) comprise a critical trafficking machinery which mediates endosomal protein sorting. Retromer and/or SNX dysfunction has been linked to several neurodegenerative diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD) and Down’s syndrome (DS). In AD, deficiency of the retromer complex or its cargo proteins impairs endosomal trafficking of amyloid precursor protein (APP), resulting in the overproduction of β-amyloid (Aβ). Several SNX components directly interact with APP or APP-cleaving enzymes (- and γ-secretases) to regulate amyloidogenic APP processing and Aβ generation. In addition, PD-linked mutations in retromer components cause mistrafficking of retromer cargo proteins and mitochondrial dysfunction, and dysregulation retromer-mediated trafficking has been considered as an important cause of hereditary spastic paraplegia (HSP) and neuronal ceroid lipofuscinoses (NCLs). Moreover, SNX27 deficiency is an important contributor for synaptic and cognitive impairment in DS. Here we review recent findings describing the retromer complex and/or SNXs-mediated endosomal sorting in neurodegenerative disorders.